State of Internet of Things Deployment in Africa and its Future: The Nigerian Scenario - Ndubuaku, Maryleen; Okereafor, David (LINK Centre, University of the Witwatersrand (Wits), Johannesburg, 2015)
Internet of things (IoT) refers to an intelligent network of connected objects for the purpose of communication, actuation,data aggregation and information processing. Currently in Africa there is a slow rate of adoption of IoT compared with other continents. Nigeria, as the biggest mobile market and most populous African country, has enormous prospects in IoT, which if effectively implemented, is likely to bring about increased productivity across all economic sectors and an improved standard of living for the people. This paper looks at the current state of IoT deployment in Nigeria, the challenges faced and the opportunities that abound.